2019
DOI: 10.1002/adfm.201908075
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular MXene Arrays with Periodic Interspaces toward Dendrite‐Free Lithium Metal Anodes with High‐Rate Capabilities

Abstract: Although lithium metal is an ultimate anode material for lithium-based batteries owing to its high theoretical capacity, the uncontrollable dendrites and infinite volume change associated with poor rate capabilities are stagnating its practical applications. Here, a new type of perpendicular MXene-Li array is developed with tunable MXene walls and constant space in between as anodes for lithium metal batteries. Such perpendicular MXene arrays possess dual periodic interspaces, i.e., nanometer-scale interspaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 32 publications
1
61
0
Order By: Relevance
“…[22] Theh ydroxylated MXene (h-MXene) materials possess fibrous morphology and more content of oxygenic functional groups,c ompared with twodimensional MXene materials, [23][24][25][26][27] as well as high electric and thermal conductivity. [28][29][30] Among all the MXene materials,T i 3 C 2 is most typical one and has been widely studied. [24] Previous studies have shown that loading with oxygenic functional groups can improve the sodiophilic/lithiophilic nature of the carbon hosts,r esulting in relatively low overpotential for Na/Li nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…[22] Theh ydroxylated MXene (h-MXene) materials possess fibrous morphology and more content of oxygenic functional groups,c ompared with twodimensional MXene materials, [23][24][25][26][27] as well as high electric and thermal conductivity. [28][29][30] Among all the MXene materials,T i 3 C 2 is most typical one and has been widely studied. [24] Previous studies have shown that loading with oxygenic functional groups can improve the sodiophilic/lithiophilic nature of the carbon hosts,r esulting in relatively low overpotential for Na/Li nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…The perpendicular MXene arrays could not only Reproduced with permission. [214] Copyright 2020, Wiley-VCH.…”
Section: Mxene Arrays For Li-metal Anodementioning
confidence: 99%
“…Recently, Yang and co‐workers designed perpendicular MXene–Li arrays with adjustable MXene walls and constant space in between by a rolling‐cutting method ( Figure a). [ 214 ] They first fabricated a flexible Ti 3 C 2 T x MXene film by a vacuum filtration method. Then the MXene film and Li strip were pressed together and manually rolled into a MXene–lithium cuboid.…”
Section: The Application Of Mxene In Metal Anodesmentioning
confidence: 99%
“…In order to facilitate fast ion transport and fully utilize the active surface, several strategies have been proposed to overcome the restacking problem, such as adding "spacers" between MXene layers [14][15][16] , creating pores [17][18][19][20] , establishing three-dimensional (3D) structures and fabricating vertical alignments [21][22][23][24][25] . Fabricating 2D MXene nanosheets into 3D structure has been focused as a significant and effective approach for increasing the ion accessibility to the active sites, and many ways have been reported including template methods [ 13 , 26 , 27 ], freeze-drying [28][29][30] , loading on 3D matrix [31][32][33] .…”
Section: Introductionmentioning
confidence: 99%